Aging exercise of young adult individuals based on photographs of biological parents - Hassan, Hayati Abu (Universiti Sains Malaysia, 2016)
A person's face is one of the important features for identification. Age is one of the main challenges encountered in face recognition, identification and age estimation. Facial aging is a dynamic process involving the aging of soft tissue and bony structures. The aim of this research is to propose a scientific method of aging young adults to old individuals based on their biological parents. The aging was demonstrated with the aid of Adobe® Photoshop® CS6. Aging of the face is accomplished by taldng an image of the individual and adding features such as wrinkles, freckles, sagging skin, or removing of hair and colour. The results obtained were compared with the parents to determine the reasonability of the aged photographs. Results indicate the possibility of using photographs of parents to age the young adults.